The service-oriented enterprise : learn enterprise architecture and its viable services - Graves, Tom (Apress, 2023)
A service-oriented architecture is fundamental to many new IT applications, from web development to social software and cloud computing. The same principles can be applied to every aspect of the service-oriented enterprise not just in IT. In this book, youll explore how an enterprise architecture and viable services can link together to create a simpler yet far more powerful view of the enterprise, as a dynamic, unified whole. You can use the ideas, principles and methods described here in business transformation, workflow mapping, system design and much else besides, in every type of enterprise - including those in which there may be little or no IT at all. Step by step, youll walk through the basics of service-oriented architectures, the four key categories of services and how they connect, and how all of this comes together in real-world service design, implementation and operations. From this, youll discover how to identify and describe the different types of services that you need for your enterprise, and how to distinguish between the services that you can safely outsource, versus those that you do need to keep in-house. By the end of this book, youll learn how to construct function models and service models of your enterprise as a base for service-mapping, and how to pinpoint and map the information flows you need for service-management and service-performance, to keep everything on-track to purpose. You will: See how an enterprise architecture can work as a literal architecture Understand Stafford Beers "Viable System Model" and adapt it as a robust model Study how a Viable Services Model provides a template for service design that covers functionals, non-functionals and operational governance for services.